2018
DOI: 10.1002/adbi.201800088
|View full text |Cite
|
Sign up to set email alerts
|

Halophiles as Chassis for Bioproduction

Abstract: Industrial biotechnology aims to solve the challenges of petroleum‐based production using microorganisms as catalysts. However, current industrial biotechnology suffers from high energy and fresh water consumption as well as difficult downstream purification. In addition, most industrial microorganisms are not resistant to other microbial contaminations, and this seriously compromises process effectiveness and the economy. The recently proposed “next‐generation industrial biotechnology” employs contamination r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 159 publications
(119 reference statements)
0
27
0
Order By: Relevance
“…Over the next decades, new microbial chasses will need to be developed that can derive carbon from alternative sources, such as plastic waste, or CO 2 from the atmosphere either directly or by coupling to an inorganic "artificial leaf" [96][97][98][99] . Fresh water is also a limited resource that is heavily used in fermentation and halophilic chases could be developed that grow in bioreactors containing ocean water 100 . Cell-free manufacturing offers the potential to reduce the water usage, physical footprint and cellular uncertainty 31,101 .…”
Section: What Else Does the Future Hold?mentioning
confidence: 99%
“…Over the next decades, new microbial chasses will need to be developed that can derive carbon from alternative sources, such as plastic waste, or CO 2 from the atmosphere either directly or by coupling to an inorganic "artificial leaf" [96][97][98][99] . Fresh water is also a limited resource that is heavily used in fermentation and halophilic chases could be developed that grow in bioreactors containing ocean water 100 . Cell-free manufacturing offers the potential to reduce the water usage, physical footprint and cellular uncertainty 31,101 .…”
Section: What Else Does the Future Hold?mentioning
confidence: 99%
“…Several studies have reported successful PHA production by photosynthetic bacteria such as cyanobacteria and purple bacteria [17, 18]. Additionally, PHA producers derived from marine bacteria and halophiles could also reduce production costs and lower contamination risk by using seawater as culture media [1921]. A few research groups have been focusing on marine photosynthetic purple bacteria, which have the additional advantage of the ability to grow and biosynthesize PHA under microaerobic conditions [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported successful PHA production by photosynthetic bacteria such as cyanobacteria and purple bacteria [14, 15]. Additionally, PHA producers derived from marine bacteria and halophiles could also reduce production costs and lower contamination risk by using seawater as culture media [1618]. A few research groups have been focusing on marine photosynthetic purple bacteria, which have the additional advantage of the ability to grow and biosynthesize PHA under microaerobic conditions [19, 20].…”
Section: Introductionmentioning
confidence: 99%